Efficacy of high-dose methylprednisolone and cyclophosphamide in childhood-onset systemic lupus erythematosus - Putu Ayunda Trisnia; Ketut Dewi KUmara Wati; Komang Ayu Witarini; Ida Bagus Ramajaya Sutawan; Hendra Santoso (Paediatrica Indonesiana, 2020)
Background Systemic lupus erythematosus (SLE) is a chronic, multisystem, autoimmune disease. Untreated SLE often become progressive and lead to increased risk of mortality. Corticosteroid and cyclophosphamide remain the treatment of choice for severe SLE. Disease activity assessed with SLE Daily Activity Index (SLEDAI).